Predicting the risk of Alaria alata infestation in wild boar on the basis of environmental factors. (April 2022) - Klich, Daniel; Nowicki, Marek; Didkowska, Anna; Bełkot, Zbigniew; Popczyk, Bartłomiej; Wiśniewski, Jan; Anusz, Krzysztof
Abstract: Alaria alata is an emerging parasite that poses a potential risk for those consuming game, pork, snails and frogs. One paratenic host of A. alata that is known to play an important role in its spread through its feeding habitats is the wild boar. However, no statistical analysis of the influence of aquatic environments and carnivores on the occurrence of A. alata in wild boars has yet been performed. The present study combines a small-scale analysis based on hunting districts in the Mazowieckie province with a large-scale analysis based on data for all provinces in Poland. We applied various modeling approaches, including logistic regression and a generalized linear model in order to determine the presence, intensity and prevalence of A. alata. We used the Alaria mesocercariae migration technique (AMT) to estimate the risk of A. alata among wild boar in a given hunting district or province. The small-scale analysis found that mesopredators (red fox ( Vulpes vulpes )) and racoon dog ( Nyctereutes procyinoides ) were likely to influence A. alata infestation of wild boar; however, the effect was weak, probably as a result of the large home range size of these animals. The large-scale analysis found that wetlands influence the prevalence of A. alata in wild boar, with the estimated risk increasing in the north of the country; this finding is consistent with other studies. Our findings indicate that the occurrence of A. alata in wild boar requires analysis on many levels, and environmental factors play a key role in risk assessment. Graphical abstract: Image 1 Highlights: Alaria alata presence in wild boar was locally dependent on the red fox density. Intensity of Alaria alata could be predicted locally by raccoon dog density. Wetlands were significantly explaining the occurrence of Alaria alata in voivodeships. Risk of Alaria alata prevalence in wild boar in Poland increase to the north.